Hierarchical twinning and light impurity doping enable high-performance GeTe thermoelectrics. (1st January 2022) - Tsai, Yi-Fen; Ho, Meng-Yuan; Wei, Pai-Chun; Wu, Hsin-Jay
Abstract: Microstructure engineering fulfilled by phase transformation elicits the reduced thermal conductivity κ in thermoelectric materials. We demonstrate that the multiscale hierarchical twinning structure could exist in the GeTe alloys as the phase transformation from cubic β -GeTe to rhombohedral α -GeTe is manipulated by two-step cooling. The coexistence of nanoscale and microscale herringbone structures yields the low-lying κ, attributing to the reorientation of martensitic variants and pile-up of martensitic twinning. Dilute dopants of Cu and Bi/Sb further suppresses hole carrier concentration n H to the order of 10 20 cm −3, leading to the enhanced power factor PF  =  S 2 ρ − 1 of α -GeTe. Meanwhile, the phase diagram engineering probes the solubility limit of Cu in the single-phase GeTe, diminishing the formation of undesired impurity phases. These strategies boost the peak zT value to 1.5 at 698 K in the light-doped Bi0.01 Cu0.01 Ge0.98 Te alloy. The multiscale twin hierarchy and carrier optimization synergistically enhance the thermoelectric performance of GeTe-based alloys that provide a new chapter in search of green energy resources out from phase change materials. Graphical abstract: Image, graphical abstract